Digital Transformation of Banking Marketing in Current Circumstances - N. I. Bykanova (Вестник Российского экономического университета имени Г. В. Плеханова)
Digital transformation taking place in all sphere of human life quickly changes the approach to fixing marketing communications, as specific weigh of off-line marketing communications decreases from year to year. In view of the fact that banking sector is an engine of digital and technological solutions, banks can adapt to needs of today’s clients shaped in conditions of digital transformation. Analysis of academic investigations dealing with introduction of banking products and services of e-commerce, advanced digital technologies, internet-banking and mobile banking into market shows that these elements have not been thoroughly studied but at the same time they are needed and interesting for clients. The article identifies transformation landmarks of banking marketing development depending on globalization reforms in economy. Evolution analysis of today’s concept, i. e. digital marketing was carried out and high dynamics of developing information technologies on banking service market was revealed.